2003
DOI: 10.1590/s0066-782x2003000200007
|View full text |Cite
|
Sign up to set email alerts
|

Can patients with left main coronary artery disease wait for myocardial revascularization surgery?

Abstract: or = 50%) consecutively identified on diagnostic cardiac catheterization during an 8-month period were selected for the study. The group comprised 56 patients (40 males and 16 females) with a mean age of 61±10 years. The cardiac events included death, nonfatal acute myocardial infarction, acute left ventricular failure, unstable angina, and emergency surgery. RESULTS: While waiting for surgery, patients experienced the following cardiac events: 7 acute myocardial infarctions and 1 death. All events occurred wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…They reported that myocardial infarction within 7 days before surgery, preopera-tive renal failure, ejection fraction of less than 40%, age greater than 70 years and stenosis of LMCA greater than 70% were independent predictors of the worse outcome. Da Rocha and da Silva (2003) reported that only unstable angina independently predicted worse outcomes in patients with LMCA stenosis. Virani et al (2006) reported that only unstable angina or myocardial infarction was associated with worse oucome in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that myocardial infarction within 7 days before surgery, preopera-tive renal failure, ejection fraction of less than 40%, age greater than 70 years and stenosis of LMCA greater than 70% were independent predictors of the worse outcome. Da Rocha and da Silva (2003) reported that only unstable angina independently predicted worse outcomes in patients with LMCA stenosis. Virani et al (2006) reported that only unstable angina or myocardial infarction was associated with worse oucome in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Although percutaneous coronary intervention can be performed for unprotected LMCA stenosis, surgery is still the preferred method of treatment in most centers (Tan et al 2001;Takagi et al 2002). Studies performed to find out the optimal operating time for patients with LMCA disease are limited and have given contraversial results (Maziak et al 1996;Gol et al 2000;Da Rocha and da Silva 2003;Legare et al 2005;Virani et al 2006). Although some studies report that the risk is not increased as preoperative waiting time prolongs, they were not primarily focused on the patients with LMCA stenosis (Morgan et al 1998;Rexius et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…6,8,11,13 Our findings contrast with others that have suggested that stenosis of the left main coronary artery may be associated with an increased risk of death. 4,14 However, many of these studies were limited by their small size (n = 56-90). Supporting our findings of no association with increased mortality were results from a large study involving more than 5864 consecutive patients waiting for CABG.…”
Section: Discussionmentioning
confidence: 99%
“…Rocha и соавт. среди 56 пациентов с поражением ствола ЛКА, находя-щихся на листе ожидания КШ, у 7 определялись неблаго-приятные кардиальные события (6 инфарктов миокарда и 1 смерть) [22]. Стратификация пациентов по экстренно-сти выполнения КШ не позволила предотвратить смерт-ность в период ожидания операции.…”
Section: клинико-морфологическая характеристика ибс у пациентов с порunclassified